Capital structure and its determinants in companies originating from two opposite sides of the European Union: Poland and Portugal - Czerwonka, Leszek; Jaworski, Jacek (Economics and Business Review, 2022)
The aim of the paper is to identify differences in enterprises’ capital structure and its determinants in Poland and Portugal. The research applies statistical methods to the financial data of 22,775 Polish enterprises and 36,625 Portuguese enterprises for the years 2010–2017. The research results show that: (i) despite several years of ongoing economic integration in the EU differences in enterprises’ capital structure in old and new countries of the community still exist, (ii) in Portugal representing the old EU enterprises are more likely to use debt than in Poland being an emerging EU economy, (iii) in Polish enterprises, tangibility, profitability, liquidity and non-debt tax shield exert a negative impact on debt; while growth and size have a positive impact; in Portugal tangibility and a non-debt tax shield show the opposite, (iv) in both countries industry growth decreases indebtedness of enterprises while financial risk results in higher debt; in addition, in Portugal the capital intensity of industry increases the share of debt in capital structure.